Kajian Tentang Pengurusan Sisa Bahan Binaan di Tapak Bina di Johor - Muryanto, Muzhafera Murni; Khalid, Zailawati; Borham , Zaharuddin; Masrom, Md. Asrul Nasid; Sarpin, Norliana (Research in Management of Technology and Business, 2023)
Nowadays, construction activities are one of the main activities in the development of the country. Construction activities in Malaysia are also growing due to construction projects carried out by construction companies. Nevertheless, the waste of building materials is seen to have an impact on the sustainability of the country's economy, the environment, cost productivity and can reduce the overall performance of the project. Piles of building material waste also occur because of poor management. Therefore, this study aims to identify the contractor's compliance with the rules in managing construction material waste, examine the problems in managing construction material waste throughout the project carried out at the construction site in Johor and identify effective management methods that have been carried out for construction material waste in Johor. Qualitative methods were used to collect data and information by conducting interview sessions with G7 contractors consisting of project managers, executive directors and contract directors. A total of five respondents were involved in this study. The findings of the study found that the contractor's compliance with the rules in managing construction material waste is the preparation of construction material waste separation and collection points, the preparation of construction material waste collection points, obligations towards transport service vehicles transporting construction material waste, obligations regarding records of collected construction material waste, the provision of construction solid waste collection bins and the obligation to appoint licensees for transport services. While the problem in managing construction material waste at the construction site throughout the project is a lack of communication between the parties involved in managing construction material waste. Next, the effective method that has been done for construction material waste at the construction site is the reuse of waste and the prevention and reduction of construction material waste. Therefore, this study is important in helping contractors to manage construction material waste on construction sites more consistently and effectively in the future.